Perlindungan Hak Perempuan dalam Hukum Keluarga Islam Kontemporer di Indonesia: Perspektif Maqasid al-Shari‘ah - Roisul Malik; Dwi Runjani Juwita (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The protection of women's rights in Islamic family law is a crucial issue that continues to evolve along with social, cultural, and technological changes in contemporary Muslim societies. Although Islam has normatively established the principles of justice, equal dignity, and protection of women's human rights, family law practices in various countries still demonstrate a gap between normative ideals and implemented realities. This article aims to analyze the concept of protecting women's rights in contemporary Islamic family law, emphasizing the relationship between normative texts, classical Islamic jurisprudence (fiqh) constructs, and the contextual needs of modern society.This research employs a normative legal research method with conceptual, philosophical, and legislative approaches. Data were obtained through a literature review of primary sources, including the Qur'an, Sunnah, and classical Islamic jurisprudence (fiqh), as well as secondary sources, including legislation, religious court decisions, and contemporary academic studies. The analysis was conducted qualitatively, emphasizing the maqāṣid al-sharī‘ah approach as the primary theoretical framework for assessing the protection of women's rights.The research findings indicate that Islamic family law has strong normative potential in guaranteeing women's rights, such as rights in marriage, divorce, maintenance, child custody, and property ownership. However, rigid textual interpretations, the dominance of patriarchal culture, and weak regulation and law enforcement often hinder the realization of substantive justice for women. In the contemporary context, new challenges such as digital marriage, polygamy without principles of justice, and domestic violence demand a renewal of Islamic family law thinking that is more responsive and oriented toward the public interest.This article asserts that the protection of women's rights in contemporary Islamic family law must be guided by a contextual ijtihad approach that integrates the values of the maqāṣid al-sharī‘ah, gender justice, and human rights principles. Thus, Islamic family law functions not only as a religious norm but also as an instrument of legal protection that is adaptive, humanistic, and relevant to the needs of modern society.